TINJAUAN KEMBALI KEBERADAAN "KANAL" DI KOTA MAJAPAHIT - Sugeng Riyanto (Berkala Arkeologi, 2010)
Many researchers believe that the capital city of Majapahit was eguipped with intersected canals. This network of canals varies in its width, between 40 â€” 80m, and its depth was between 6 â€” 9 m. There are at least five canals strecthing in north - south direction and seven canal in east - west direction. The canals were cleariy described in many reports and publications as if their existence have been proved. In fact, the vestiges of this network of â€œcanalsâ€ have never been examined thoroughly. Therefore, the lucid visual description of this â€œcanal networkâ€ is actually untested yet. In oder to give more factual picture on the canals network, in 2007 the National Research Centre and Development of Archaeology conducted a field survey to trace back the actual condition of the canal. This article reports the result